Neo-tanshinlactone selectively inhibits the proliferation of estrogen receptor positive breast cancer cells through transcriptional down-regulation of estrogen receptor alpha. (September 2016) - Lin, Wanjun; Huang, Jiajun; Liao, Xiaolin; Yuan, Zhongwen; Feng, Senling; Xie, Ying; Ma, Wenzhe
Graphical abstract: Abstract: Breast cancer, the most frequent cancer in women, is the second leading cause of cancer-related death. Estrogens and estrogen receptors are well recognized to play predominant roles in breast cancer development and growth. Neo-tanshinlactone is a natural product isolated from Salvia miltiorrhiza and showed selective growth inhibition of ER+ breast cancer cell lines as demonstrated by cell proliferation assay and colony formation assay. The selective anti-proliferative effect of neo-tanshinlactone was associated with the induction of apoptosis in ER+ breast cancer cells. We also found that neo-tanshinlactone decreased steady state ESR1 mRNA levels in ER+ breast cancer cells, which was further confirmed by analysis of ER protein levels as well as the mRNA levels of target genes of this transcription factor, such as ESR2, BRCA1, CCND1, GREB1, TFF1, SERPINB9 and ABCA3 . Furthermore, analysis of heterogeneous nuclear RNA (hnRNA) demonstrated that neo-tanshinlactone inhibited ESR1 mRNA de novo synthesis. The decrease of steady state ESR1 mRNA upon neo-tanshinlactone treatment was not abolished by protein synthesis inhibitor cycloheximide. And inhibition of mRNA synthesis with actinomycin D revealed no significant effect of neo-tanshinlactone on ESR1 mRNA stability. These results indicated that transcriptional down-regulation of ESR1 mRNA could contribute to the selective activity of neo-tanshinlactone on ER+ breast cancer cells. And as expected, the combination of neo-tanshinlactone and antiestrogen reagent tamoxifen showed a synergistic effect on growth of ER+ MCF7 cells. Our results suggest that neo-tanshinlactone is a promising regimen for ER+ breast tumors.